The Economic Analysis for Construction in Ibn Khalduon s’ Muqaddimah - فرحان, اسيا كاظم; مطلك, هيثم حميد (Journal of Economics and Administrative Sciences, 2018)
The specialist researcher  fined the relations between economic ideas with economic facts in his theory which called humanity building it is appeared clearly ( in Ibn Khalduons’ Muqaddimah) in a clothe of economic  social  phenomenon's as a systematical analysis in all fifty chapters of al Muqaddimah ,therefore this paper deal with  Ibn Khalduon economic thoughts as important says which describe the society building in its economic subjective  and  examine the relationship between The dissert and the city within economic says which are cover  the social analysis ,and determinate   the analysis objects  which clearly in this dualism  model ,between the state and economic base(Al mash ) ,so that Ibn Khalduon see the  dramatic  economic changes from  the dessert to  the city .Ibn Khalduon now how the civilization growth and decline by the economic factor which consider by Ibn Khalduon the first and greatest accomplish to classify the tow environments belongs  to the ways   to the human get there  living from using the nature  (means of production )  which leads to  the production collections ,clearly growth within times. it is so much relatively to the conditions which role the tow  economical model in  society  at  fourteen  century  in morocco kingdoms .this paper leads us to describe and analyze the most  important    factors to decline the civilization of Morocco at that period by the economic factor which Ibn Khalduon thought it by the consumption civilization  model because of destroying all capitalization in the two environments and didn’t moving to the capitalism system , therefore Ibn Khalduon ideas  pattern to historical economical development of societies ,as a scientific method